Spatio-Temporal Expression Profile of Stem Cell-Associated Gene LGR5 in the Intestine during Thyroid Hormone-Dependent Metamorphosis in Xenopus laevis - Sun, Guihong (Public Library of Science, 2010)

(untitled)
BACKGROUND: The intestinal epithelium undergoes constant self-renewal throughout adult life across vertebrates. This is accomplished through the proliferation and subsequent differentiation of the adult stem cells. This self-renewal system is established in the so-called postembryonic developmental period in mammals when endogenous thyroid hormone (T3) levels are high. METHODOLOGY/PRINCIPAL FINDINGS: The T3-dependent metamorphosis in anurans like Xenopus laevis resembles the mammalian postembryonic development and offers a unique opportunity to study how the adult stem cells are developed. The tadpole intestine is predominantly a monolayer of larval epithelial cells. During metamorphosis, the larval epithelial cells undergo apoptosis and, concurrently, adult epithelial stem/progenitor cells develop de novo, rapidly proliferate, and then differentiate to establish a trough-crest axis of the epithelial fold, resembling the crypt-villus axis in the adult mammalian intestine. The leucine-rich repeat-containing G protein-coupled receptor 5 (LGR5) is a well-established stem cell marker in the adult mouse intestinal crypt. Here we have cloned and analyzed the spatiotemporal expression profile of LGR5 gene during frog metamorphosis. We show that the two duplicated LGR5 genes in Xenopus laevis and the LGR5 gene in Xenopus tropicalis are highly homologous to the LGR5 in other vertebrates. The expression of LGR5 is induced in the limb, tail, and intestine by T3 during metamorphosis. More importantly, LGR5 mRNA is localized to the developing adult epithelial stem cells of the intestine. CONCLUSIONS/SIGNIFICANCE: These results suggest that LGR5-expressing cells are the stem/progenitor cells of the adult intestine and that LGR5 plays a role in the development and/or maintenance of the adult intestinal stem cells during postembryonic development in vertebrates.